2022
DOI: 10.5194/esd-13-231-2022
|View full text |Cite
|
Sign up to set email alerts
|

Weakened impact of the Atlantic Niño on the future equatorial Atlantic and Guinea Coast rainfall

Abstract: Abstract. The Guinea Coast is the southern part of the West African continent. Its summer rainfall variability mostly occurs on interannual timescales and is highly influenced by the sea surface temperature (SST) variability in the eastern equatorial Atlantic, which is the centre of action of the Atlantic Niño mode. Using both historical and scenario (SSP5–8.5) simulations from 31 general circulation models (GCMs) participating in the sixth phase of the Coupled Model Intercomparison Project (CMIP6), we first s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 67 publications
5
21
0
Order By: Relevance
“…The enhanced low-level convergence over the warm oceanic area is accompanied by an ascent of moist air, which is then advected by the low-level circulation towards the Guinea Coast. This provides favourable conditions for the rainfall occurrence over this region (Polo et al, 2008;Rodríguez-Fonseca et al, 2015;Schubert et al, 2016;Lübbecke et al, 2018;Worou et al, 2020Worou et al, , 2022. Over the 1901-2016 period, the eastern equatorial Atlantic positive correlation with the rainfall over the Guinea Coast was stationary during the boreal summer (Losada et al, 2012;Diatta and Fink, 2014;Worou et al, 2020).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…The enhanced low-level convergence over the warm oceanic area is accompanied by an ascent of moist air, which is then advected by the low-level circulation towards the Guinea Coast. This provides favourable conditions for the rainfall occurrence over this region (Polo et al, 2008;Rodríguez-Fonseca et al, 2015;Schubert et al, 2016;Lübbecke et al, 2018;Worou et al, 2020Worou et al, , 2022. Over the 1901-2016 period, the eastern equatorial Atlantic positive correlation with the rainfall over the Guinea Coast was stationary during the boreal summer (Losada et al, 2012;Diatta and Fink, 2014;Worou et al, 2020).…”
Section: Introductionmentioning
confidence: 90%
“…The changes of the equatorial Atlantic mean state under the highest greenhouse gas emission scenario (SSP5-8.5) lead to a weakened variability of the AEM in the future (Worou et al, 2022;Crespo et al, 2022;Yang et al, 2022). Worou et al (2022) showed a projected weakening of the trade winds climatology over the equatorial Atlantic and a deeper thermocline in the 365 eastern equatorial Atlantic which would lead to a reduction of the coupling between the surface and the thermocline depth.…”
Section: (A)(g))mentioning
confidence: 99%
See 3 more Smart Citations